Energy Transformation Within the Framework of Sustainable Development and Consumer Behavior - Anna Szeląg-Sikora; Aneta Oleksy-Gębczyk; Józef Ciuła; Mariusz Cembruch-Nowakowski; Katarzyna Peter-Bombik; Paulina Rydwańska; Tomasz Zacłona (Energies)
The energy transition currently defines the economic development of all market sectors, driven by technological progress and increasing environmental awareness. The requirements of a sustainable economy and green energy are evolving dynamically to address environmental challenges, emphasizing the reduction of CO2 emissions as well as energy efficiency and renewable energy sources. It is essential to study consumer attitudes toward products manufactured using green energy, including FMCG (fast-moving consumer goods) products. The aim of this article is to examine the impact of the energy transformation, and consequently rising energy costs, on the decision-making process of consumers of FMCG products produced in accordance with the principles of sustainable development (including green energy). It explores the factors influencing their purchasing decisions and the role that generation plays in this process. Understanding how different generations respond to the energy aspects of economic functioning is crucial for the future development of the energy sector and the implementation of sustainable economic models. Therefore, it is essential to conduct research that demonstrates the extent of the influence of increasing consumer awareness of energy transformation within the framework of sustainable development.